From Flanders to Pernambuco: Battleground Perceptions in the Portuguese Early Modern Atlantic World. (July 2019) - Dantas da Cruz, Miguel
This article addresses the way the Portuguese experience in the seventeenth-century battlefields of Flanders, during the Iberian Union (1580–1640), reshaped Portuguese military thought and culture. It argues that their traditional martial perceptions – almost exclusively based in imperial experiences, especially against the Muslims in North Africa and in India – were transformed by the direct exposure to Spanish military endeavours in Europe. It also argues that the experience in Flanders resurfaced in the South Atlantic, in all its religious and political dimensions, transforming the prestige of Brazil as a battlefield. Finally, the article revisits the way the Flanders experience poisoned Spanish–Portuguese relations.